City Environment and Occurrence of Neural Autoantibodies in Psychiatric Patients - Hansen, Niels; Juhl, Aaron Levin; Grenzer, Insa Maria; Teegen, Bianca; Wiltfang, Jens; Fitzner, Dirk (Frontiers in Psychiatry, 2022)
Background: City living might lead to higher risk of psychiatric disease, but to date there is no evidence of any correlation between an urban environment and the occurrence of neural autoantibodies in psychiatric disease. Our aim is to identify whether the numbers of patients with and without neural autoantibodies living in diverse rural and urban environments differ. Methods: We enrolled retrospectively a cohort of 167 psychiatric patients via a cross-sectional design from the Department of Psychiatry and Psychotherapy University Medical Center Göttingen and determined serum and/ or CSF neural autoantibodies in them. The patients live in the German states of Lower Saxony, Thuringia, and Hessen. Their data were investigated in conjunction with the location of their primary residence. We categorized them in five different categories depending on their primary residence: one rural and four different urban environments depending on their population numbers. Results: We identified 36 psychiatric patients with neural autoantibodies, and 131 psychiatric patients with none. 24 psychiatric patients with neural autoantibodies were classified as sharing a possible, probable, or definitive autoimmune origin according to our recently-set criteria. We observed as a non-significant trend that more psychiatric patients with neural autoantibodies and a probable or definitive autoimmune origin (45.8%) live in a major city with over 100 000 inhabitants than do psychiatric patients presenting no evidence of autoantibodies (26.4%). However, we identified no relevant differences between (1) psychiatric patients with and without neural autoantibodies or between (2) psychiatric patients with a possible, probable, or definitive autoimmune origin and those without such autoantibodies in relation to the diverse rural and urban environmental settings. Conclusions: The inherently different aspects of rural and urban environments do not appear to be relevant in determining the frequency of neural autoantibodies in psychiatric patients in Lower Saxony, Thuringia and Hessen in Germany. Further large-scale studies involving other states across Germany should be conducted to exclude any regional differences and to examine the tendency of a higher frequency in large cities of autoimmune-mediated psychiatric syndromes.